Esmolol improves sepsis outcomes through cardiovascular and immune modulation - Jing, Da; Xiong, Li; Zhang, Rong; Fang, Hong; Chen, Lin (Frontiers in Pharmacology, 2025)
BackgroundSepsis poses significant mortality risks. Esmolol, a β1-adrenergic blocker, may improve outcomes through cardiovascular and immune modulation. This study aims to evaluate the effects of Esmolol on survival rates, inflammatory markers, and immune function in sepsis patients.MethodsIn this retrospective observational study, data from 268 sepsis patients were reviewed, and 125 met the inclusion criteria. These patients were divided into Esmolol and control groups. Data were collected from electronic health records, including survival rates, inflammatory markers (IL-6, PCT), and immune function markers (CD4+ and CD8+ T-cell counts). Statistical analyses included multivariate regression, Kaplan-Meier survival analysis, and Generalized Estimating Equations.ResultsThe Esmolol group demonstrated significantly higher survival rates at both 14 days (80% vs. 41.67%, p < 0.01) and 28 days (75.38% vs. 30.00%, p < 0.01) compared to the control group. The median ICU stay was longer in the Esmolol group (12 days vs. 10 days, P = 0.045). Significant reductions in heart rate (P = 0.002), NE levels (P = 0.036), and inflammatory markers were observed in the Esmolol group. Additionally, Esmolol treatment resulted in bidirectional regulation of T-cell counts, increasing CD4+ and CD8+ T-cell counts in patients with higher baseline immune function and decreasing these counts in patients with lower baseline levels (P < 0.01).ConclusionEsmolol improves survival rates and clinical outcomes in sepsis patients, particularly those with higher baseline immune function. The benefits are attributed to early and prolonged administration of Esmolol, highlighting its potential as a valuable addition to sepsis treatment protocols. Future multicenter trials are needed to confirm these findings and refine the use of β1AR in sepsis management.Clinical Trial Registration:clinicaltrials.gov, identifier NCT06390748.